DESIGN AND PERFORMANCE EVALUATION OF A 50 WP OFF-GRID SOLAR PV TRAINER KIT AS AN INSTRUCTIONAL MEDIUM IN VOCATIONAL EDUCATION - Rion Michael Potoe; Silvy Dollorossa Boedi; I Gede Para Atmaja (EDUCATIONE, 2026)
Renewable energy has become a global priority to reduce dependence on fossil fuels, with solar power offering significant potential, particularly in equatorial countries like Indonesia. Despite abundant solar energy resources, its utilization remains limited, underscoring the need for educational interventions that build technical competencies in renewable energy. This study aims to design, construct, and evaluate the performance of a 50 Wp off-grid Solar Photovoltaic (PV) Trainer Kit as an instructional medium for vocational and higher education laboratories. The research employed a design-based approach consisting of planning, product design, fabrication, and testing. The trainer kit integrates essential components including a polycrystalline solar module, inverter, charge controller, VRLA battery, and monitoring devices. Performance testing was conducted using true outdoor experimental methods, focusing on solar radiation intensity, charging efficiency, and discharging duration. Results indicate that under clear weather conditions, the trainer achieved full battery charging in 3.5 hours, while battery discharge under a 100 W AC load lasted approximately one hour. These findings confirm the trainer’s functional reliability and its potential as an effective learning medium. The study concludes that the developed trainer kit not only enhances practical learning of photovoltaic systems but also supports national efforts in renewable energy education. The research recommends further development with larger solar module capacity and alternative battery types to expand instructional applications.